Ambedkar’s Controversial Views on Indigenous Peoples: A Discussion - Bhattachan, Krishna B. (Nepal Journal of Sociology, 2025)
Dr. Bhimrao Ramji Ambedkar is a luminary who requires no introduction today, for his enduring legacy, ideology and significant relevance continue to inspire not only the Dalit community but also those outside of it. His thoughts resonate widely, transcending the borders of India. Among the numerous facets of Ambedkar recognized by many, his thoughts and position regarding Indigenous Peoples remain largely unrecognized and undiscussed, and I have never come across this discussion in Nepal. Indeed, both Ambedkar and Indigenous Peoples voice common perspectives: de-Brahmanize, de-colonize, de-construct, re-right and re-write. However, despite this shared understanding, there are specific issues with how Ambedkar perceives and describes Indigenous People, as his choice of words are seen as problematic, derogatory and unacceptable. Furthermore, it cannot be justified by merely subscribing to those defensible opinions, arguing that Ambedkar should be understood within his time and context. This critical essay broaches a discussion regarding this particular line of reasoning, evaluating both Ambedkar and his followers, while simultaneously challenging the perception of who is savage and who is civilized.